2021
DOI: 10.3389/fcvm.2021.669110
|View full text |Cite
|
Sign up to set email alerts
|

Modest Gains After an 8-Week Exercise Program Correlate With Reductions in Non-traditional Markers of Cardiovascular Risk

Abstract: Background: Although engaging in physical exercise has been shown to reduce the incidence of cardiovascular events, the molecular mechanisms by which exercise mediates these benefits remain unclear. Based on epidemiological evidence, reductions in traditional risk factors only accounts for 50% of the protective effects of exercise, leaving the remaining mechanisms unexplained. The objective of this study was to determine whether engaging in a regular exercise program in a real world clinical setting mediates c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Several other studies have investigated the effect of exercise training on fibrinolysis, but the results are conflicting. Two non-randomised studies reported a reduction in PAI-1 and thereby an increased fibrinolysis after 8 weeks or 9 months of exercise 9 23. In contrast, three non-randomised studies found no changes in PAI-120 24 or tissue plasminogen activator9 24 after regular exercise training.…”
Section: Discussionmentioning
confidence: 96%
“…Several other studies have investigated the effect of exercise training on fibrinolysis, but the results are conflicting. Two non-randomised studies reported a reduction in PAI-1 and thereby an increased fibrinolysis after 8 weeks or 9 months of exercise 9 23. In contrast, three non-randomised studies found no changes in PAI-120 24 or tissue plasminogen activator9 24 after regular exercise training.…”
Section: Discussionmentioning
confidence: 96%
“…86 Additionally, a study conducted by Liang et al noted that improvements in physical activity, physical fitness, and/or weight loss were associated with decreased procoagulation parameter production, including plasma levels of PAI-1. 87 Thus, weight reduction through diet and exercise may have some beneficial effects on the imbalance of coagulation/fibrinolysis pathways in obesity, but these effects on asthma pathology remain unclear.…”
Section: Coagulation In Obesitymentioning
confidence: 99%